ANALISIS FAKTOR PEMBENTUK BAURAN PEMASARAN PADA NASABAH BANK BNI SYARIAH CABANG PADANG - Aulia Agusatria; Abel Tasman (Jurnal Ecogen, 2018)
This study aims to analyze the factors forming the marketing mix at BNI Syariah customers in Padang Branch. This type of research is quantitative descriptive. The population of this research is customers of Islamic banks in the city of Padang with a sample of 100 customers obtained using Slovin formula. The sampling technique is accidental sampling. Research data are primary data collected by questionnaire. Instrument testing uses validity and reliability tests. Data were analyzed by descriptive analysis and factor analysis. The results of the study showed that of the eight factors there were six factors that influence the form of the marketing mix for customers of the BNI Syariah branch of Padang Branch.Keyword: Marketing Mix